Intrathecal Baclofen for Severe Spasticity: Longitudinal Data From the Product Surveillance Registry. Issue 7 (27th January 2020) - Schiess, Mya Caryn; Eldabe, Sam; Konrad, Peter; Molus, Lisa; Spencer, Robert; Stromberg, Katherine; Weaver, Todd; Plunkett, Robert
Abstract : Objective: To assist in the assessment of intrathecal baclofen (ITB) therapy risks and benefits by providing surgical intervention rate, safety, and elective device replacement rate data. Materials and Methods: An ongoing prospective, long‐term, multicenter Product Surveillance Registry (PSR) (NCT01524276) enrolled consented patients implanted with the SynchroMed II infusion system. Pump and catheter performance data were collected, with patients followed prospectively for events related to the device, procedure, and therapy. Investigators provided event descriptions, patient symptoms, and patient outcomes. Results: We analyzed registry data from 1743 patients (77% adult, 46.8% female) treated with ITB for severe spasticity at 53 registry sites between August 2003 and October 2017, for an accumulated 6481 patient‐years. Discontinuation from the registry was largely (58.6% of discontinued patients) due to study site closure and patient relocation; exit due to an adverse event was limited to 0.3%. After 10 years, 87.2% of adult and 76.3% of pediatric patients continued with ITB. Overall, 99.1% of pumps reaching end of battery life were replaced at the time of explant. Conclusions: ITB therapy for the treatment of severe spasticity requires surgical implantation of a programmable infusion system for chronic drug delivery. If complications arise, many necessitate surgical intervention for correction. For spinal and cerebral spasticity in pediatric and adult patients, discontinuation rates due to an adverse event were low (0.3%), and there was high acceptance (99.1%) of surgical intervention for therapy continuation. Patient/caregiver willingness to accept surgical and other risks for therapy continuation was extremely high.